Consensual Pupillometry for Robotic Emotional Recognition - Fekete, Róbert Tamás; Raj, Levente; Neumer, Tamas (Recent Innovations in Mechatronics, 2015)
The main contribution of this research is to develop of a new measuring device for measuring direct- and consensual light reflex of human pupil. In this case the pupillary light reflex means changing of diameter of pupil due to constant light stimulus as a function of time. Researches certify that the pupil diameter and its change reflects the person’s mental or physical state. There are several “eye tracking” devices available on the market, however, none of these are able to perform a proper consensual measurement. The basic principle of the consensual pupil measurement is that while only one of the eyes is stimulated, reactions of both eyes are being recorded and analyzed. The aim of this project was to develop a software, applicable to an existing prototype device in order to carry out “consensual pupillary reflex” measurements.